Cancer patients’ control preferences in decision making and associations with patient-reported outcomes: a prospective study in an outpatient cancer center - Schuler, Markus K.; Trautmann, Freya; Schmitt, Jochen Maximilian (Supportive care in cancer, 2017)
Purpose“Shared decision making” has been proposed as a prerequisite of patient-centered care. However, little is known on factors, which may influence cancer patients’ decision control preferences (DCP) in routine care. This study investigated possible determinants of the patients’ DCP with respect to patient characteristics and patient-reported outcomes (PROs).MethodsConsecutive patients presenting at a comprehensive cancer center between May 2014 and October 2014 were offered a self-administered electronic questionnaire including standardized PRO measures and patients’ DCP. Results were linked with patient characteristics from the hospital information system and analyzed using cross-sectional methods.ResultsOut of 126 patients participating, 102 (81%; 65% male; mean age 62 years) completed the DCP-item. Overall, 49% (n = 50) preferred shared treatment decision responsibility, 29% (n = 30) preferred to leave the control to his/her physician, whereas 22% (n = 22) preferred to be in control of his/her treatment decision. Higher age (p = 0.035) and elevated distress levels (p = 0.038) were significantly associated with an increased willingness to leave the decision control to the physician. Further sociodemographic and PRO measures were not associated with patients’ DCP.ConclusionOur findings demonstrate that DCP assessment in routine cancer care is possible and provides important information to the treating oncologist. Information on DCP combined with PRO may contribute to more individualized decision making in cancer care.